Development Toward an Impact Resistance Test on Glass Fiber Reinforced Polymer (GFRP) Grating - Hambali, Nurul Nasyihah (Universiti Teknologi Petronas, 2012)
The major problems deals with steel usage at offshore structures are corrosion and excessive bulk weight. The corroded structure has to replace with new ones while heavier platform needs a lot of equipment for loadout, transport and install. These causes huge increment in cost. Therefore, the researchers came with an alternative to replace steel with an advance composite material such as Glass Fiber Reinforced Polymer (GFRP). GFRP is a composite material consists of continuous glass fiber embedded in resin matrix. The resistance impact test must be conducted to check the ability of the GFRP grating toward high impact. Therefore, an impact testing rig becomes an essential tool for such research activities but there is no specific standard available to meet this objective. This paper is focused on design of drop weight testing rig and development toward GFRP grating impact resistance test. The research is the emphasis on mechanical design of the drop weight testing rig. The rig has load impactor, guided by two 2.75m I-beam columns, which can impact the grating up to 1373.4 J. Using Eurocode 3 as reference; the details design of the testing rig is produced. The testing rig is designed to meet the impact test parameters which are adjustable drop heights, variable impact loads and using 1.25m x 1.25m GFRP grating.